Creating Positive Partnerships for Agricultural Programs Within Native Nations in Oklahoma - Jann Hayman (Adult Education Research Conference, 2023)
This research looks at the agricultural systems of four Oklahoma-based Native nations and the College of the Muscogee Nation, while looking at how partnerships impact the development of these programs.
Keywords: Native nation agriculture; Indigenous leaders; agricultural partnerships